Additional Financing to the Agriculture and Natural Resources Landscapes Management Project (SUSTENTA) - World Bank (World Bank, 2019)
Proposed Development Objective(s) Parent The project development objective is to integrate rural households into sustainable agriculture and forest-based value chains in the Project area and, in the event of an Eligible Crisis or Emergency, to provide immediate and effective response to said Eligible Crisis or Emergency. Components Agriculture and Forest-Based Value Chain Development Securing Land Tenure Rights and Increasing Natural Resources Resilience Project Coordination and Management Contingency Emergency Response
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; governance / governação; land governance / gestão de terra; natural resources / recursos naturais

Independent Report of the Extractive Industries Transparency Initiative - EITI (Extractive Industries Transparency Initiative (EITI), 2019)
This is the ninth report reconciling payments made by companies operating in the extractive industry and receipts from the State. 97% of tax revenues from the extractive industry were reconciled. The differences between the payments by the companies and the receipts from the State correspond to 0,17% of the amounts confirmed by the State in 2019
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais